Clothes that Click Workbook - Joy Cantrell Jordan; R. Nadine Hackler (EDIS, 2002)
This document is 4H CCM 12, of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Reviewed, June 2002.